Uji Tingkat Akurasi Model Prediksi Kebangkrutan pada Perusahaan Sektor Kesehatan di Bursa Efek Indonesia Tahun 2012-2022 - Rusadi, Lia Atthahira; Mukhzarudfa, Mukhzarudfa; Friyani, Rita (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The purpose of this research is to determine the level of accuracy or accuracy of the Altman Z-Score, Fulmer, Grover, Springate, Taffler, Zavgren and Zmijewski models in predicting bankruptcy in Health sector companies listed on the Indonesia Stock Exchange. The period of years in this study is 2012 to 2022. This type of research used is a descriptive quantitative design. The population in this study amounted to 33 health sector companies. Then the sample of this study amounted to 9 with a period of 11 years which resulted in a total of 99 samples with the sampling process using the sampling method to be used in this study is the judgment sampling method, which is one form of purposive sampling. The data used is secondary data in the form of company financial reports from the website www.idx.co.id. The grover and fulmer model is determined as the most accurate model in predicting the bankruptcy of Health sector companies listed on the Indonesia Stock Exchange based on the results of this study with a score of 100%. The next model is the zavgren model with a score of 94.95%, and the zmijewski model with a score of 92.93%. Furthermore, followed by the springate model with a score of 83.84%, the taffler model of 70.71% and the last place is occupied by the altman z-score model with an accuracy score of only 53.54%.